(untitled) (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2025)
The Biopond Machine Black Soldier Fly Maggot Separator (BIOMASTOR) technology is an integrated system for cultivating maggots and KUB chickens, designed to address livestock management challenges faced by Ahmad Hidayah Farm partners. One of the main challenges in maggot cultivation is the inefficient process, as it still relies on floor bioponds. In particular, the separation of maggots from their digestive waste (cashgots) requires an additional transfer process to a sieve, making it less effective. Meanwhile, challenges in KUB chicken farming include the suboptimal utilization of chicken manure, which contributes to environmental pollution, as well as the high cost of commercial concentrate feed, leading to increased production expenses. This community service program aims to implement an integrated system for maggot farming and KUB chicken rearing through Integrated Smart Farming at Ahmad Hidayah Farm. The program activities include outreach to partners, training on technology usage, and direct application of BIOMASTOR technology by partners. Following implementation, partners successfully applied the Integrated Smart Farming system, followed each stage according to instructions, and optimized the use of BIOMASTOR technology. The achieved outcomes include: (1) Efficient separation of 100 kg of cashgots in just 15 minutes, (2) Utilization of chicken manure as a growth medium for maggots, reducing chicken manure waste by up to 95%, (3) Replacement of commercial concentrate feed with protein-rich maggots, leading to a 50% reduction in concentrate feed purchases. — Teknologi Biopond Machine Black Soldier Fly Maggot Separator (BIOMASTOR) merupakan teknologi integrasi budidaya maggot dengan ayam KUB untuk mengatasi permasalahan sistem peternakan pada mitra Ahmad Hidayah Farm. Permasalahan mitra terjadi pada proses budidaya maggot yang kurang efektif karena masih menggunakan biopond lantai, terutama pemisahan maggot dengan sisa pencernaannya (kasgot) yang memerlukan proses pemindahan ke ayakan terlebih dahulu. Sedangkan permasalahan pada peternakan ayam KUB yaitu kurang optimalnya pemanfaatan kotoran ayam yang dapat mencemari lingkungan, serta mahalnya harga pakan konsentrat yang menyebabkan tingginya biaya produksi. Tujuan pengabdian kepada masyarakat adalah untuk mengimplementasikan sistem integrasi peternakan maggot dengan ayam KUB melalui Integrated Smart Farming pada usaha Ahmad Hidayah Farm. Metode pengabdian dilakukan melalui kegiatan sosialisasi pada mitra, pelatihan penggunaan teknologi, dan penerapan teknologi oleh mitra. Hasil pelaksanaan kegiatan pihak mitra mampu menerapkan sistem integrated smart farming, melaksanakan tiap tahapan sesuai dengan arahan, dan menggunakan teknologi BIOMASTOR dengan optimal. Output yang diperoleh diantaranya; (1) Waktu pemisahan maggot dengan kasgot yaitu 100 kg kasgot dalam waktu 15 menit. (2) Limbah kotoran ayam dimanfaatkan menjadi media pertumbuhan dan perkembangan maggot, dapat mengurangi limbah kotoran ayam mencapai 95%. (3) Pembelian pakan ayam konsentrat diganti dengan maggot yang memiliki kandungan protein, menekan pembelian pakan konsentrat sebesar 50%.